EFFICIENT INTRODUCTION OF COMPLEMENTARY FOODS FOR CHILDREN WITH ATOPIC DERMATITIS AND PREDISPOSITION TO ALLERGIC REACTIONS FOR PREVENTION OF ATOPIC MARCH - A.V. Kamaev (Union of pediatricians of Russia, 2011)
Prevalence of allergic diseases grows constantly. Realization of genetic defects to the disease depends of impact of environment and contacts with different allergens. Prophylactic dietary avoidance is important to prevent debut of the atopic dermatitis and secondary exacerbations of the disease. Terms and preferable sequence of complementary food introduction are discussed for breast-fed and formula-fed infants; advantages of ready-made industrial products of infant meals are proved. The gradual outreach of infant's taste spectrum and increasing step by step of load on infant's intestine can become serious hedge for the atopic march and important measure of prevention of allergic rhinitis and asthma.Key words: atopic march, dietetics, complementary foods, prevention of allergies, children.